Irritable bowel syndrome among High School Students, Bagdad, Iraq, 2017-2018 - Hazaa, Hanaa F.; Lami, Faris H. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Irritable Bowel Syndrome (IBS) is a common chronic functional gastrointestinal disorder characterized by abdominal pain or discomfort and alteration in bowel habits. It is more common among adolescents and young age groups. Objectives: to estimate the prevalence and identify potential determinants of IBS among high school students in Baghdad, Iraq, 2017. Methods: This cross-sectional study was conducted by using multi-staging cluster probability sampling technique. All students in the sixth grade were considered eligible. Students with "red flag" symptoms were excluded. Rome III criteria questionnaire of IBS was considered to define IBS. A self-administered questionnaire used to compile socio-demographics, personal habits and certain potential determinants. IBS was further classified as mixed type (M-IBS), diarrhea predominant type (D-IBS) and constipation predominant type (C-IBS). Result: Among 657 eligible high school students, 592 (90.1%) were enrolled. The prevalence of IBS was 29.7% (95% C.I: 29.4- 30.1%). The most common type of IBS was M-IBS (42.6%) followed by D-IBS (33.5%). Binary and logistic regression analyses revealed the following significant factors: exposure to stressful life event (OR: 3.93; 95% CI: 2.64 – 4.85), food hypersensitivity (OR: 2.89; 95% CI: 1.59 – 3.27), chronic diseases (OR: 2.22; 95% CI: 1.24 – 3.95), family history of IBS (OR: 2.04; 95% CI: 1.30 – 3.01) and female sex (OR: 1.84; 95% CI: 1.25 – 2.73). C-IBS was significantly more common among females (P=0.02) Conclusion: IBS is a common health problem among high school students. Among the hereditary, environmental and psycho-social factors, stress was the most important determinant.